The Melody Lingers On - Clark, Mary Higgins; Maxwell, Jan; Pearlman, Karen; Simon & Schuster Audio (Firm) (New York : Simon & Schuster Audio, 2015)
A beloved aunt's agreement to help her niece with college essays reawakens past secrets about the night a grandparent was murdered, an event that compels the woman to investigate a treasured music box to uncover the truth.
Keywords: Cold cases (Criminal investigation) -- Fiction; Family secrets -- Fiction; Rich people -- Fiction; Audiobooks; Suspense fiction; Mystery fiction; Audiobooks